Rietveld analysis of computed tomography and its application to methanol to olefin reactor beds. (1st December 2015) - Wragg, David Stephen; O'Brien, Matthew G.; Di Michiel, Marco; Lønstad‐Bleken, Francesca
Abstract : This article reports the creation of tomographic reconstructions giving three‐dimensional data on the distribution of various structural features for SAPO‐34 zeolite catalyst beds used in the commercially important methanol to olefin conversion process. The data were processed using parametric Rietveld refinement to treat entire slices of the tomograph as single refined data sets, allowing extraction of real structural parameters from all voxels of the reconstruction. This has the advantage over more traditional methods of X‐ray diffraction computed tomography using peak intensities, that the structural parameters are independent of the intensity, meaning that information can still be extracted from poor data sets: an example is shown where part of the sample was no longer in the beam during data collection. Reconstructions using several structural parameters are presented and the results compared. Analysis of the variation of the catalyst c axis (linked to the degree of deactivation in earlier work) shows small but significant three‐dimensional variations in the degree of deactivation with patterns which depend on the silicon content of the catalyst. Average data for the tomographic slices compare well with the results of earlier operando two‐dimensional reactor scanning experiments.